THE INFLUENCE OF SMART BOARD GAMES ON THE ROUGH MOTOR DEVELOPMENT OF CHILDREN AGE 4 TO 5 YEARS - Kristin Anggraini (Magister Scientiae, 2020)
The aim of this study was to develop children's gross motor development through playing. This research used quantitative research methods with quasi experimental -nonequivalent control group design. In this study, the researcher used four research instruments, namely running, jumping, hopping and throwing. The results of this study indicated positive influences of the Smart Board game on the gross motor development. This was evidenced by the significant difference between the results of the pretest and posttest on children's gross motor skills, especially in terms of running, jumping, hopping and throwing in children aged 4-5 years. When playing, the children gained experience, pleasure and knowledge and through this one form of playing that could increase children's knowledge as well as develop the gross motor aspects of children is the Smart Board game. This study showed that this Smart Board game could be used to develop children's gross motor development well, especially for running, jumping, hopping and throwing in children aged 4-5 years.